LEVEL FEASIBILITY MEDIA LEARNING SYSTEM AIR CONDITIONER (AC) TO INCREASE LEARNING RESULT - Bambang Sudarsono (Jurnal Taman Vokasi, 2018)
This study aims to determine the feasibility level of learning media Air Conditioner system (AC) which has been developed through the research stages that adopted research development of Sugiyono. The subject of the research is the students of Automotive Engineering Study Program of Muhammadiyah University of Purworejo semester 4. From the development stage it can be seen that the validity by the material experts and the media expert reaches a score above 75% with valid category. Once applied, achievement outcomes increased 79.20 for the experimental class and 67.20 for the control class. So it can be concluded learning media AC system developed feasible to use and can improve learning outcomes.